Penguatan Literasi pada Anak Kelas 2 Melalui Pendekatan Kreatif Pembelajaran Huruf "b" dan "d" - Fathatun Fathatun (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This study was conducted to evaluate the effectiveness of a creative learning approach in enhancing the understanding of the letters "b" and "d" among second-grade students at Sekolah Dasar Negeri 1 Sidigede. The research background is rooted in the challenges faced by some students in distinguishing the letters "b" and "d." The research aim is to identify whether the creative learning approach can contribute positively to the understanding of these letters. The research employed an experimental design with a control group, involving 20 students. The data analysis revealed a significant improvement in letter comprehension scores in the experimental group. Classroom observations noted active participation and positive responses to the creative activities implemented in the learning process. The study's conclusion asserts that the creative learning approach is effective in enhancing letter literacy for "b" and "d" among second-grade students. The practical implication of this research is that the application of creative strategies can be a beneficial alternative in the context of teaching letters to children at this level.